A critical review of current evidence on multiple types of discrimination and mental health - Vargas, Sylvanna M; Huey, Stanley J; Miranda, Jeanne (American journal of orthopsychiatry, 2020)
Little is known about people who experience multiple types of discrimination (e.g., racism and heterosexism). While some work suggests that multiply discriminated groups are at higher risk for poor mental health, other studies propose that they may develop resilience against additional kinds of discrimination. We conducted a review of published studies on the relationship between multiple types of discrimination and mental health to critically examine evidence in support of broad risk and resilience models. Using PRISMA guidelines, we identified 40 studies that met our inclusion criteria. Typically, studies examined either whether experiencing multiple discrimination was related to poorer mental health, or whether one kind of discrimination was more predictive of poor mental health. Studies generally showed support for the risk model, with multiple forms of discrimination associated with higher risk for depression symptoms. Furthermore, both racism and heterosexism uniquely predicted symptoms of depression, although initial evidence suggested that only heterosexism predicted suicidality among lesbian, gay, bisexual, transgender, and queer (LGBTQ) racial/ethnic minorities. Findings on multiple discrimination and other mental health problems (e.g., anxiety, posttraumatic stress disorder [PTSD], distress, and substance use) were mixed. The current evidence suggests that multiply discriminated groups exhibit higher risk for some mental health problems, particularly depression symptoms. However, methodological problems abound in this literature (e.g., correspondence between study sample and types of discrimination assessed), which limits our ability to draw clear conclusions about multiple discrimination. We propose that to further our understanding of how multiple kinds of discrimination may affect mental health, studies must remedy these and other issues. (PsycInfo Database Record (c) 2020 APA, all rights reserved).